"Not just another Wii training": a graded Wii protocol to increase physical fitness in adolescent girls with probable developmental coordination disorder-a pilot study - Emmanuel Bonney; Eugene Rameckers; Gillian Ferguson; Bouwien Smits-Engelsman (BMC, 2018)
Abstract Background Adolescents with low motor competence participate less in physical activity and tend to exhibit decreased physical fitness compared to their peers with high motor competence. It is therefore essential to identify new methods of enhancing physical fitness in this population. Active video games (AVG) have been shown to improve motor performance, yet investigations of its impact on physical fitness are limited. The objective of this study was to examine the impact of the graded Wii protocol in adolescent girls with probable Developmental Coordination Disorder (p-DCD). Methods A single-group pre-post design was conducted to assess the impact of a newly developed Wii protocol in adolescent girls attending school in a low income community of Cape Town, South Africa. Sixteen participants (aged 13-16 years) with p-DCD (≤16th percentile on the MABC-2 test) were recruited. Participants received 45 min Wii training for 14 weeks. Outcome measures included the six-minute walk distance and repeated sprint ability. Information on heart rate, enjoyment and perceived exertion ratings were also collected. Results Significant improvements in aerobic and anaerobic fitness were observed. The participants reported high enjoyment scores and low perceived exertion ratings. The graded Wii protocol was easily adaptable and required little resources (space, equipment and expertise) to administer. Conclusions The findings provide preliminary evidence to support the use of the graded Wii protocol for promoting physical fitness in adolescent girls with p-DCD. Further studies are needed to confirm these results and to validate the clinical efficacy of the protocol in a larger sample with a more robust design.